Le Bestiaire d’amour de Gustave Flaubert (1) - Loïc Windels (Flaubert: Revue Critique et Génétique)
In The Legend of Saint Julian the Hospitalier – the middle of Flaubert’s Three Tales – to desire and to kill are but one thing, and its Map of Tendre encroaches somewhat on the topographies of Cruelty. He who looks into his bestiary is usually rather quick to detect its symbolic character and pre-Freudian overtones. It is as if Flaubert did with Medieval legends what Freud would do a little later with Greek mythology. These observations and other similar ones have already been made, and there is no doubt that the reader who loves the dense and suggestive prose that is The Legend of Saint Julian is familiar with them. Thus, the present article (and the one that will follow) strive less to reopen an already well-fed debate than to approach it in a slightly different manner: namely, by choosing from amongst the episodes where animals play a leading role, those which seem to pair up to form – by leaps and gambols – a narrative behind the story and those which, at the same time, appear desirous of being compared to other texts (the rest of Flaubert’s work, Medieval bestiaries, ancient and modern natural history, mythological writings) and a few images.